VALIDATION OF THE MALAY-TRANSLATED EXPECTANCY VALUE MODEL QUESTIONNAIRE AND MULTI-DIMENSIONAL SPORTSPERSONSHIP ORIENTATIONS SCALE AMONG MALAYSIAN ADOLESCENCE FIELD HOCKEY PLAYERS - Kanagarajah Rarujanai; Teo Eng Wah; Arthur Ling; Ngien Siong Chin; Mansur Mansur (LPMPP Universitas Negeri Yogyakarta, 2020)
This study presents an overview of Malaysian adolescent field hockey players’ expectancy beliefs, subjective values and sportspersonship attitude. We aimed to translate and validate two questionnaires i.e., Expectancy Value Model Questionnaire (EVMQ) and Multi-dimensional Sportspersonship Orientations Scale (MSOS) to Malay language. The EVMQ and MSOS were translated into the Malay language using the back translation method. A total of 230 respondents (15.40 ± 2.17 years) were recruited for this study. The result of analyses are EVMQ-M (M = 5.38 ± .95) and MSOS-M (M = 3.64 ± .40) respectively. Content validity was checked by experts in the fields for content conformity and culture bias whereas face validity was confirmed by ten participants. Both questionnaires showed high internal consistency (reliability); EVMQ-M (α = .94) and MSOS-M (α = .82). Data fits were checked using the Structural Equation Model; EVMQ-M (χ² (df = 39) = 84.07, CFI = .97, GFI = .94, TLI = .95, RMSEA = .07, ChiSq/df = 2.16) and MSOS-M (χ² (df = 146) = 321.76, CFI = .92, GFI = .87, TLI = .90, RMSEA = .07, ChiSq/df = 2.20) also showed good construct validity. The translated Malay version EVMQ-M and the MSOS-M are reliable and valid instruments to assess Malaysian adolescent field hockey players.